The Effect of Online Customer Experience Towards Repurchase Intention - Yusepaldo Pasharibu; Eristia Lidia Paramita; Gea Stephani (International Journal of Supply Chain Management, 2018)
Internet users develop rapidly in a developing country, such as Indonesia. Therefore, it will change the consumer behavior, mainly the way of transaction, which is from conventionally to electronically that called as e-commerce. Moreover, one of the objectives that all business either conventional or online want is to achieve the loyal consumer. The indicator of the loyal consumer mainly determines through repurchase intention that can be chasing while they can give their customers a positive experience. This study aimed to observe the effect of customer experience toward repurchase intention in one of a favourite e-commerce site in Indonesia, called as Tokopedia. A quantitative method with 200 respondents conducted in this research. Thus the data were analysed using multiple linear regressions technique. The findings of this study showed that customer experience variables, including sense, feel, act and relate positively influenced to repurchase intention, whereas, variable think had no affected to the repurchase intention.